STRATEGI PENGEMBANGAN OBYEK WISATA MELALUI PENDEKATAN COMUNITY BASED TOURISM DI PANTAI LAWATA KOTA BIMA TAHUN 2024 - Khairunisyah, Khairunisyah; Siti Atika Rahmi; Yudhi Lestanata; Mustamin H. Idris; Mintasrihardi, Mintasrihardi (Nusantara Hasana Journal, 2025)
This study aims to analyze the development strategy of Pantai Lawata tourism object in Bima City through the Community Based Tourism (CBT) approach. The background of this research is based on the great potential of Pantai Lawata as a leading tourist destination with natural beauty, good accessibility, and diverse local culture, but it has not been optimally managed. The CBT approach was chosen because it emphasizes the empowerment of local communities in the planning, management, and implementation of tourism, so that economic and social benefits can be directly experienced by the local community. The research method used is qualitative with data collection techniques through observation, interviews, and documentation. The informants of this research consist of local government, tourism entrepreneurs, community members, and visitors of Pantai Lawata. Data were analyzed using the interactive model of Miles and Huberman, including the stages of data collection, data reduction, data display, and conclusion drawing. The results show that the development strategies of Pantai Lawata through CBT include: enhancing community participation in tourism planning and management, developing nature- and culture-based attractions, improving the quality of amenities and accessibility, implementing digital-based promotion, and strengthening partnerships between the government, community, and private sector. Supporting factors of this strategy are natural beauty, strategic location, and government support. Meanwhile, inhibiting factors include limited supporting facilities, low capacity of local human resources, and suboptimal promotion.